PERSEPSI GURU SEKOLAH DASAR TERHADAP KEBERHASILAN IMPLEMENTASI KURIKULUM 2013 - Apri Damai Sagita Krissandi (Universitas Muhammadiyah Surakarta, 2018)
Abstract: This study aimed to describe the perception of elementary school teachers Kanisius Branch of Central Java and Yogyakarta about the success in implementing the curriculum 2013. This study was descriptive research. The subjects were 65 teachers in Central Java and Yogyakarta under the Kanisius Foundation. The data were collected through questionares and interviews. The instrument validity was assessed by triangulation methods. The data were analyzed using the descriptive analysis technique. The results of the study show that the succes in 2013th curriculum implementation were government, institution, teacher, parent and student. The success that comes from the teacher has a percentage of 27.5%. Student-generated success has a percentage of 31.2%. Successes from the government have a percentage of 15.9%. The success that comes from the institution has a percentage of 10.9%. Finally, the success that comes from parents has a percentage of 14.5%.